A case-control study of perfluoroalkyl substances and the risk of breast cancer in Taiwanese women. (September 2020) - Tsai, Meng-shan; Chang, Shu-Han; Kuo, Wen-Hung; Kuo, Ching-Hua; Li, Szu-Yi; Wang, Ming-Yang; Chang, Dwan-Ying; Lu, Yen-Shen; Huang, Chiun-Sheng; Cheng, Ann-Lii; Lin, Ching-Hung; Chen, Pau-Chung
Highlights: PFOS was associated with breast cancer risk in Taiwanese women. Young women (age ≤ 50 years) had a high risk of breast cancer by PFOS exposure. Women in the age less than 50 years had a higher risk of estrogen receptor positive tumors than those in the age over 50 years by PFHxS and PFOS exposure. Abstract: Breast cancer (BC) is a common cancer in women worldwide; however, the incidence of BC is increasing in younger women, possibly associated with the environment. Perfluoroalkyl substances (PFAS) are one of endocrine disruptors that accumulate in environment and impact human health. This study aimed to investigate whether the PFAS and BC are associated. We enrolled 120 BCE patients and 119 controls at National Taiwan University Hospital (NTUH) and also collected bio-specimen and questionnaire from 2013 to 2015. All subjects' plasma PFAS levels were analyzed by ultra-performance liquid chromatography tandem mass spectrometry method with electrospray ionization (UHPLC-ESI-MS/MS). A logistic regression model was used to estimate the association between PFAS and BC. In the ≤50 years age group, the adjusted odds ratio (OR) was 2.34 (95% CI = 1.02, 5.38) for perfluorooctane sulfonate (PFOS) exposure per natural log unit increase. After stratifying the estrogen receptor (ER) status and age group, we obtained a positive association for PFHxS and PFOS concentrations with respect to the risk of ER positive tumors for ≤50 years age group. In conclusion, we found that PFAS were associated with the BC risk of ER positive tumors in young Taiwanese women. Further studies are needed to follow and explore whether these associations are causal.